Analytical solution for cylindrical bending of two-layered corrugated and webcore sandwich panels. (February 2018) - Pydah, Anup; Batra, R.C.
Abstract: We analytically investigate infinitesimal cylindrical bending deformations of two-layered triangular corrugated and webcore linearly elastic sandwich panels by using the mechanics of materials approach and the classical plate theory. The model is validated by comparing its predictions with the solution by the finite element method of the linear elasticity equations for plane strain deformations. The model can accurately capture the secondary bending of the facesheets, manifested as changes in their curvature between the webs and the resulting changes in the axial stresses, from being tensile to possibly compressive, that the commonly-employed homogenization schemes fail to capture. Subsequently, the model is used to analyze several problems with the sandwich panel having a pinned support at the left edge and a roller support at the right edge, and a uniformly distributed load applied on the top facesheet of the panel. It is found that the core plates mostly deform in compression and bending, respectively, for corrugated and web core panels. Furthermore, a significant fraction of the work done by the external load on the structure is absorbed as strain energy of deformations of the core plates near the supports. For four hybrid combinations of corrugated and webcore configurations in two-layered panels, the combination with the upper corrugated core set-up has the least maximum face sheet deflection and axial stress. The analytical technique can be easily extended to multi-layered hybrid configurations and provides quick means of finding efficient strain-energy absorbing hybrid designs. Abstract : Highlights: Webs of a corrugated core (webcore) deform primarily in compression (bending). Significant fraction of the applied load is carried by core webs located near the supports. Hybrid corrugated core designs have least facesheet deflections and stresses. Hybrid webcore designs absorb large fraction of the work done by the applied loads.